The theory of employment: two approaches compared - Roncaglia, Alessandro (PSL Quarterly Review, 2014)
Introducing the publication of a long 1956 letter by Franco Modigliani (FM) to Paolo Sylos Labini (PSL) on the draft of PSL’s book, Oligopoly and Technical Progress, the paper critically reviews the theoretical background of FM’s comments, showing how the pre-Keynesian roots dominate the so-called neoclassical synthesis as well as its shaky foundations. The paper also discusses FM’s interpretation of PSL’s oligopoly theory, as well as their collaboration (and differences) on policy issues, such as their opposition to the 100% money wage indexation adopted in Italy from the mid-1970s to the mid-1980s. Keywords: Macroeconomic theory, Oligopoly, Neoclassical synthesis, Modigliani, Sylos Labini JEL code: B31, D43, E13, E64